Analisis Capital Budgeting terhadap Kelayakan Investasi Aktiva Tetap pada UD. Syam Jaya di Desa Klatakan Kecamatan Tanggul Kabupaten Jember - Maulana, Rizal Ade; Ika Sari, Maheni; Hasan afidzi, Achmad (Universitas Muhammadiyah Metro, 2024)
The aim of this research is to conduct a capital budgeting analysis of the feasibility of permanent activation investment at UD. Syam Jaya Jember Regency. The research variables to be analyzed are grouped into four variables, namely Payback period, Net present value, Profitability Index and Fixed Asset Investment. This research method is based on exploratory descriptive, with qualitative research using a case study approach. The data is in the form of quantitative data (numbers), but the approach uses qualitative analysis because this research will produce descriptive data. In accordance with the problems and objectives to be achieved in this research, it can be concluded from the calculation results that they are as follows: 1) The payback period for the old investment is 2 years 7 months, while the new investment produces a payback period of 1 year 10 months. And this is illustrates that new investments are more feasible because they have a faster return on investment than old investments. 2) The Net Present Value of the new investment is IDR 280,981,859 and the Net Present Value of the old investment is IDR 116,157,732, which means that if you look at the NPV value itself, the NPV of the new investment is greater than the NPV of the old investment . 3) The Profitability Index (PI) of the old investment is 1.2 and the Profitability Index of the new investment is 1.5. This implies that both investments generate profits for the company. So the new investment that the company will make is worthy of replacing the old investment.